USE OF NULLOMERIC DNA SEQUENCE IN DEVELOPMENT OF REAL-TIME PCR TEST SYSTEMS - Tynysbekov , B.K.; Auganov , A.N.; Akhmetollayeva , A.S.; Akhmetollayev, I.A. (Eurasian Journal of Applied Biotechnology, 2025)
This study describes the development of a real-time PCR (qPCR) system for the identification of Pasteurella multocida serotypes using nullomeric DNA sequences. P. multocida is a widespread animal pathogen, and its different serogroups (A, B, D, E, and F) are directly linked to disease severity and distribution. Serotype-specific diagnostics are of great importance for disease prevention and control in veterinary practice. The main novelty of this approach lies in the use of nullomers in primer and probe design, which minimizes the risk of false-positive signals. Synthetic primers and probes were synthesized and their specificity tested against DNA from Escherichia coli, Staphylococcus aureus, and Salmonella enterica. Optimization experiments showed the most effective conditions were: MgCl₂ – 2.5 mM, dNTP – 0.5 mM and primer/probe concentration – 0.5 pM. The newly developed qPCR system demonstrated high specificity and sensitivity: it reliably detected different concentrations of P. multocida DNA (ranging from 10⁶ copies down to 1 copy/µL), with a detection threshold of approximately 100,000 copies. Serotype-specific primers produced clear amplification curves with no cross-reactivity observed. These results confirm that the use of nullomer-based primers is an effective strategy for real-time PCR diagnostics. The advantages of this method highlight its potential for application in epidemiological monitoring, veterinary diagnostics, and integration into portable qPCR platforms. The developed system enables rapid and accurate identification of P. multocida serotypes and may serve as a model for detecting other bacterial pathogens.